Just entertainment: effects of TV series about intrigue on young adults - Wang, Fei; Lin, Shengdong; Ke, Xue (Frontiers in Psychology, 2015)
The potential harmful effects of media violence have been studied systematically and extensively. However, very little attention has been devoted to the intrigue and struggles between people depicted in the mass media. A longitudinal randomized experimental group-control group, pretest–posttest design study was conducted to examine the potential effects of this type of TV series on young adults. A typical and popular TV series was select as a stimulus. By scrutinizing the outline of this TV series and inspired by studies of the effects of media violence, one behavioral observation and five scales were adopted as dependent measures. The study did not find any effect of the intrigue TV series on any of the six dependent variables. Finally, possible interference variables or moderators were discussed.